Sensory Rewiring in an Echolocator: Genome-Wide Modification of Retinogenic and Auditory Genes in the Bat Myotis davidii. Issue 10 (1st October 2014) - Hudson, Nicholas J; Baker, Michelle L; Hart, Nathan S; Wynne, James W; Gu, Quan; Huang, Zhiyong; Zhang, Guojie; Ingham, Aaron B; Wang, Linfa; Reverter, Antonio
Abstract: Bats comprise 20% of all mammalian species and display a number of characteristics, including true flight, echolocation, and a heightened ability to resist viral load that uniquely position this group for comparative genomic studies. Here we searched for evidence of genomic variation consistent with sensory rewiring through bat evolution. We focused on two species with divergent sensory preferences. Myotis davidii is a bat species that echolocates and possesses dim- but not daylight-adapted vision whereas the black flying fox ( Pteropus alecto) has highly developed day vision but does not echolocate. Using the naked mole rat as a reference, we found five functional genes ( CYP1A2, RBP3, GUCY2F, CRYBB1, and GRK7 ) encoding visual proteins that have degenerated into pseudogenes in M. davidii but not P. alecto . In a second approach genome-wide codon usage bias (CUB) was compared between the two bat species. This CUB ranking systematically enriched for vision-related ( CLN8, RD3, IKZF1, LAMC3, CRX, SOX8, VAX2, HPS1, RHO, PRPH2, and SOX9 ) and hearing-related ( TPRN, TMIE, SLC52A3, OTOF, WFS1, SOD1, TBX18, MAP1A, OTOS, GPX1, and USH1G ) machinery in M. davidii but not P. alecto . All vision and hearing genes selectively enriched in M. davidii for which orthologs could be identified also were more biased in the echolocating M. lucifugus than the nonecholocating P. vampyrus . We suggest that the existence of codon bias in vision- and hearing-related genes in a species that has evolved echolocation implies CUB is part of evolution's toolkit to rewire sensory systems. We propose that the two genetic changes (pseudogene formation and CUB) collectively paint a picture of that incorporates a combination of destruction and gain-of-function. Together, they help explain how natural selection has reduced physiological costs associated with the development of a smaller eye poorly adapted to day vision but that also contribute to enhanced dim light vision and the hearing adaptations consonant with echolocation.